Respuesta :
The answer is 49x2 _ 84x + 36
(7x - 6)² is the square of the difference. The general formula would be:
(a - b)² = a² - 2ab + b²
In our expression (7x - 6)², a would be 7x and b would be 6:
(7x - 6)² = (7x)² - 2 · 7x · 6 + 6²
= 7² · x² - 84x + 36
= 49x² - 84x + 36
(7x - 6)² is the square of the difference. The general formula would be:
(a - b)² = a² - 2ab + b²
In our expression (7x - 6)², a would be 7x and b would be 6:
(7x - 6)² = (7x)² - 2 · 7x · 6 + 6²
= 7² · x² - 84x + 36
= 49x² - 84x + 36
Answer:
option (d) is correct.
The product of [tex](7x-6)^2[/tex] is [tex]49x^2-84x+36[/tex]
Step-by-step explanation:
Given : [tex](7x-6)^2[/tex]
We have to find the product of given expression [tex](7x-6)^2[/tex]
Consider the given expression [tex](7x-6)^2[/tex]
Using algebraic identity, [tex](a-b)^2=a^2-2ab+b^2[/tex] , we get,
[tex](7x-6)^2=(7x)^2-2\cdot 7x \cdot 6+(6)^2[/tex]
Simplify ,
Using properties of exponents [tex](ab)^n=a^nb^n[/tex]
we get
[tex](7x-6)^2=49x^2-84x+36[/tex]
Thus, the product of [tex](7x-6)^2[/tex] is [tex]49x^2-84x+36[/tex]
Thus, option (d) is correct.